Analysis Of Factors Influencing The Acceptance Of Audit Opinion With Modified Going Concern - Azhari, Julia Rinnia; Hizazi, Achmad; Mansur, Fitrini (Jurnal Cakrawala Akuntansi, 2024)
This study aims to examine the effect of company growth, financial condition, and prior-year audit opinion with going concern modification on the likelihood of receiving a going concern modified audit opinion. The research focuses on manufacturing companies in the consumer goods and various industrial sectors listed on the Indonesia Stock Exchange (IDX) for the period 2015–2018. The data used are secondary data obtained from the companies’ annual financial reports. A purposive sampling technique was employed, resulting in a final sample of 75 companies. The analytical method used is logistic regression, and data were processed using SPSS version 21. The results show that company growth does not have a significant effect on the issuance of a going concern modified audit opinion. However, both the company’s financial condition and the audit opinion with going concern modification in the previous year significantly influence the likelihood of receiving a similar opinion in the current year. This study contributes to the auditing literature by providing empirical evidence on the predictors of going concern audit opinions in the Indonesian manufacturing sector. The findings highlight the importance of historical audit assessments and financial health indicators in shaping auditor judgment regarding business continuity